A Challenging Period After Repair: Etiology and Follow-Up Rates of the Patients With Cleft Lip and Palate in Intensive Care Unit. Issue 8 (7th November 2021) - Kara, Murat; Calis, Mert; Kesici, Selman; Canbay, Ozgur; Bayrakci, Benan; Ozgur, Figen
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The perioperative period is quite challenging because of the featured anatomical and clinical properties of the babies with cleft lip and palate (CLP). Therefore follow-up in the intensive care unit (ICU) is a crucial parameter for managing these patients. Although various studies in cleft literature, limited studies have analyzed the ICU admission rate and its etiology in the cleft population. At this point, the present study aims to reveal the etiology and rate of ICU admission of babies with an orofacial cleft to contribute to taking preventive precautions. The rate of primary CLP patients was 69.5% (937 of 1348 patients). Intensive care unit admission rate of primary CLP patients was 6.2% (n = 58). The expected and unexpected ICU admission rate was 4.8% and 1.4%, respectively. Of the patients admitted to the ICU, 53.4% (n = 31) were boys and 46.6% (n = 27) were girls. There was no statistically significant association between gender and ICU admission ( P  = 0.896). However, the association between cleft type and ICU follow-up was statistically significant ( P  < 0.001). The findings of the present study reveal the high ICU admission rate of cleft patients within all patients admitted to ICU. Due to many unique statuses of cleft babies, attentive assessment in the preoperative period and determining the postoperative need for ICU follow-up would contribute to preventing postoperative complications.